Screening Colonoscopy Findings Are Associated With Noncolorectal Cancer Mortality. Issue 4 (25th April 2022) - Sullivan, Brian A.; Qin, Xuejun; Miller, Cameron; Hauser, Elizabeth R.; Redding, Thomas S.; Gellad, Ziad F.; Madison, Ashton N.; Musselwhite, Laura W.; Efird, Jimmy T.; Sims, Kellie J.; Williams, Christina D.; Weiss, David; et al.
Abstract : INTRODUCTION: Controversy exists regarding the impact of various risk factors on noncolorectal cancer (CRC) mortality in healthy screening populations. We examined the impact of known CRC risk factors, including baseline colonoscopy findings, on non-CRC mortality in a screening population. METHODS: Cooperative Studies Program (CSP) #380 is comprised of 3, 121 veterans aged 50–75 years who underwent screening colonoscopy from 1994 to 97 and were then followed for at least 10 years or until death. Hazard ratios (HRs) for risk factors on non-CRC mortality were estimated by multivariate Cox proportional hazards. RESULTS: Current smoking (HR 2.12, 95% confidence interval [CI] 1.78–2.52, compared with nonsmokers) and physical activity (HR 0.89, 95% CI 0.84–0.93) were the modifiable factors most associated with non-CRC mortality in CSP#380. In addition, compared with no neoplasia at baseline colonoscopy, non-CRC mortality was higher in participants with ≥3 small adenomas (HR 1.43, 95% CI 1.06–1.94), advanced adenomas (HR 1.32, 95% CI 0.99–1.75), and CRC (HR 2.95, 95% CI 0.98–8.85). Those with 1–2 small adenomas were not at increased risk for non-CRC mortality (HR 1.15, 95% CI 0.94–1.4). DISCUSSION: In a CRC screening population, known modifiable risk factors were significantly associated with 10-year non-CRC mortality. Furthermore, those who died from non-CRC causes within 10 years were more likely to have had high-risk findings at baseline colonoscopy. These results suggest that advanced colonoscopy findings may be a risk marker of poor health outcomes. Integrated efforts are needed to motivate healthy lifestyle changes during CRC screening, particularly in those with high-risk colonoscopy findings and unaddressed risk factors.